George R. Donnan, Annotated Code of Criminal Procedure and Penal Code of the State of New York 298, § 410 (4th ed. 1885) - (:unkn) unknown (My University, 1885)
tit. 12, § 410: Prohibited using or attempting to use, carrying, concealing, or possessing a slungshot, billy, sandclub or metal knuckles, or a dagger, dirk or dangerous knife. Punishable as a felony, and as a misdemeanor if a minor.
Keywords: POSSESSION - NON-GUN ARMS